GE_GERICHTE P/24624/2020 vom 7. Mai 2021 - GE Cour de justice (2021)
IN DUBIO PRO REO;VOL(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);VIOLATION DE DOMICILE;EXPULSION(DROIT PÉNAL);DIRECTIVE 2008/115/CE | CPP.10.al2; CP.139.al1; CP.22.al1; CP.186; CP.66.leta